A Janus Hydrogel Wet Adhesive for Internal Tissue Repair and Anti‐Postoperative Adhesion. (11th September 2020) - Cui, Chunyan; Wu, Tengling; Chen, Xinyu; Liu, Yang; Li, Yuan; Xu, Ziyang; Fan, Chuanchuan; Liu, Wenguang
Abstract: Despite rapid development of adhesive hydrogels, the typical double‐sided adhesives fail to adhere to wet tissues and concurrently prevent postoperative tissue adhesion, thus severely limiting their applications in repair of internal tissues. Herein, a negatively charged carboxyl‐containing hydrogel is gradiently, electrostatically complexed with a cationic oligosaccharide by a one‐sided dipping method to form a novel Janus hydrogel wet adhesive whose two‐side faces demonstrate strikingly distinct adhesive and nonadhesive properties. The lightly complexed surface demonstrates instant robust adhesion to various wet biological tissues even under water since the phase separation induced by electrostatic complexation increases the hydrophobicity and water drainage capacity. Intriguingly, the highly complexed surface is non‐adhesive due to complete neutralization of carboxyls in the hydrogels. The Janus hydrogel can be used to replace traditional sutures to treat gastric perforation of rabbits. Animal experiment outcomes reveal that one side of the Janus hydrogel is firmly glued to the stomach tissue, and other side facing outward can efficiently prevent the postoperative adhesion. Molecular simulation elucidates the importance for selecting cationic polymer species. It is believed that gradient polyelectrolyte complexation establish a new direction to create Janus adhesives for internal tissue/organ repair and simultaneous prevention of post‐operative adhesion. Abstract : A Janus hydrogel wet adhesive with strikingly distinct adhesive/nonadhesive properties on its two sides is fabricated by gradient polyelectrolyte complexation via one‐sided dipping of a carboxyl‐containing hydrogel in cationic oligosaccharide solution. This Janus hydrogel demonstrates an instantly robust adhesion to soft tissue under water, and is successfully used for repairing perforated stomachs of rabbits, while preventing post‐operative tissue adhesion in vivo.